PENGARUH INTRINSIC MOTIVATION TERHADAP BEHAVIORAL INTENTIONS PADA STARTUP BERORIENTASI HIJAU - Ni Putu Maha Lina (JURNAL LENTERA BISNIS, 2024)
The study aims at analyzing the direct and indirect effects of intrinsic motivation, perceived ease of use, and behavioral intention on the 270 employees of eco-oriented startups in Bali. This study was conducted based on research gaps, namely: 1) the limitations of research that emphasizes intrinsic motivation in the behavioral intention of using recruitment games; and 2) the lack of studies that enrich the combination of SDT and TAM theory. The data were collected using a questionnaire with the help of SmartPLS. The results showed that: 1) Intrinsic motivation has a significant positive relationship to perceived ease of use; 2) Perceived ease of use has a significant positive relationship to behavioral intention; 3) Perceived ease of use mediates intrinsic motivation and behavioral intention; and 4) Intrinsic motivation has a significant positive relationship to behavioral intention.